SAE Technical Paper Series 2000
DOI: 10.4271/2000-01-2938
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Direct Water Injection on DI Diesel Engine Combustion

Abstract: The effects of in-cylinder water injection on a direct injection (DI) Diesel engine were studied using a computational fluid dynamics (CFD) program based on the Kiva-3v code. The spray model is validated against experimental bomb data with good agreement for vapor penetration as a function of time. It was found that liquid penetration increased approximately 35% with 23% of the fuel volume replaced by water, due mostly to the increase in latent heat of vaporization.Engine calculations were compared to experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 11 publications
1
56
0
4
Order By: Relevance
“…Additionally, water/diesel emulsion has a disadvantage that the water/fuel blend is constant over a wide range of engine operating conditions and different engine loads may require different blend ratios (Abu-Zaid, 2004). Therefore, water injection in the intake manifold and direct water injection techniques can overcome this problem (Bedford et al, 2000). However, most studies of water injection in the intake manifold confirmed that water exists in areas where it is less efficient in reducing emissions in the combustion chamber.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Additionally, water/diesel emulsion has a disadvantage that the water/fuel blend is constant over a wide range of engine operating conditions and different engine loads may require different blend ratios (Abu-Zaid, 2004). Therefore, water injection in the intake manifold and direct water injection techniques can overcome this problem (Bedford et al, 2000). However, most studies of water injection in the intake manifold confirmed that water exists in areas where it is less efficient in reducing emissions in the combustion chamber.…”
Section: Introductionmentioning
confidence: 96%
“…However, most studies of water injection in the intake manifold confirmed that water exists in areas where it is less efficient in reducing emissions in the combustion chamber. Therefore, intake manifold water injection requires approximately twice the liquid volume for the same reduction in NO x compared to direct water injection or water/fuel emulsion (Bedford et al, 2000). Tauzia et al (Tauzia et al, 2010) cited that water to fuel mass fraction of 60-65% is needed to obtain a 50% NO x reduction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the sole purpose of NO x control emissions, water can also be injected directly into the engine cylinder and vaporised, absorbing a fraction of the chemical energy hence released and then decreasing the peak temperature [7,28,29]. The latter process has been successfully applied to industrial engines, for example to some marine Diesel engines manufactured by Wärtsilä [30, page 73].…”
Section: Practical Uses Of Water Injectionmentioning
confidence: 99%